Giving Unwanted Gifts: Political Economy of Youtube Apology - Eka Sri Dana Afriza; Udi Rusadi (Sekolah Tinggi Manajemen IPMI, 2021)
A public apology is a fairly common content found on the YouTube platform to restore the reputation and regain people's trust. At the same time, Youtube can also be used as a commodity-based economic platform that allows organizations, individuals, and Google (the owner of Youtube) to earn revenue either through advertising or direct promotion. These two things reflect the dual benefits of two opposites: genuine demand in the public interest and economic exploitation for the benefit of certain parties. This is well explored by the political economy theory of media which sees the digital platform as a convergence between the moral economy of commodities, the moral economy of gifts, and the moral economy of public goods. This article aims to further explore the three elements of the political economy of the media in the context of apologies on Youtube in five cases that occurred in Indonesia. The five apology cases were analyzed using parameters reflecting the moral economy of commodities, gifts, and public goods. The results of the analysis provide a typology of apology and a model that reflects the interrelation between the three moral economies involved in every apology.